Application of UiO-66 MOF for rifampicin removal and post-adsorption antimicrobial activity against MRSA - S. A. Abdel Moaty; Amna A. Kotp; Asmaa M. Salah; Ahmed A. Farghali; Zienab E. Eldin (Scientific Reports)
Abstract Water is essential to all living forms, shaping both our planet and the human body. But their great toxicity makes dangerous contaminants like new chemicals, antibiotics, heavy metals, and microbes major dangers to water systems. This article looks at the creation and use of UiO-66, a zirconium-based metal-organic framework (MOF), as a dual-function material for rifampicin adsorption and antibacterial action. Using solvothermal techniques, UiO-66 MOFs were created and characterized by X-ray diffraction (XRD), nitrogen adsorption-desorption, field-emission scanning electron microscopy (FESEM), thermogravimetric analysis (TG), Fourier-transform infrared spectroscopy (FTIR), and Brunauer–Emmett-Teller (BET) analysis. Batch testing maximized factors like pH, starting concentration, adsorbent amount, and contact time to improve rifampicin removal effectiveness. The findings showed a maximum adsorption capacity (qmax) of 542 mg/g under ideal circumstances, suggesting UiO-66 MOF as a reasonably priced and sustainable choice for treating contaminated wastewater. Further research confirmed UiO-66’s potential as a good adsorbent for rifampicin under different settings. At lower doses, UiO-66 nanoparticle cytotoxicity on HL-7702 liver cells revealed great biocompatibility; at higher levels, it caused significant viability loss. The antibacterial effectiveness of UiO-66 MOF nanoparticles, rifampicin, and their combination against Klebsiella pneumoniae and MRSA was assessed; the combination greatly boosted antibacterial activity in comparison to separate therapies. The biocompatibility of the composite with human cells and capacity to damage bacterial cell membranes point to its possible use as an antibacterial and medication delivery system. The research offers a sustainable environmental remediation option by demonstrating that UiO-66, a zirconium-based MOF, efficiently adsorbs rifampicin from wastewater. Its high adsorption capacity of 542 mg/g points to possible treatment of MRSA and K. pneumoniae. See Fig. 1 for more details. Future studies should include property optimization, industrial application scalability, and drug interaction research.